Case Report of Puffinosis in a Manx Shearwater (Puffinus puffinus) Suggesting Environmental Aetiology - Niamh P. G. Esmonde; Robert E. B. Hanna; Jignasha G. Patel; Victoria J. Smyth; Paul Caplat; Wesley Smyth; Paris Jaggers; Oliver Padget; Tim Guilford; Chris Perrins; Neil Reid (Animals, 2022)
Puffinosis is a disease of a range of seabirds characterised by dorsal and ventral blistering of their webbed feet, conjunctivitis, dry necrosis, leg spasticity, head shaking, loss of balance, tremors, and death. It is associated with Manx shearwaters (Puffinus puffinus), frequently affecting chicks within their underground nesting burrows. The aetiology of the disease is unclear but has been attributed to a type-2 coronavirus associated with Neotombicula mites as a potential vector. However, there is some uncertainty given potential laboratory contamination with mouse hepatitis virus and failure to fulfil Koch’s postulates, with birds injected with isolates remaining healthy. We describe a detailed case report of puffinosis in a Manx Shearwater covering necropsy, histology, bacteriology, and metagenomics including viral sequencing. We found no evidence of viral infection or parasites. Our results are consistent with an entirely environmental aetiology, with caustic faecal ammonia in damp nesting burrows causing conjunctivitis and foot dermatitis breaking the skin, allowing common soil bacteria (i.e., Flavobacterium, Staphylococcus and Serratia spp., Clostridia perfringens and Enterococcus faecalis) to cause opportunistic infection, debilitating the bird and leading to death. A similar condition (foot pad dermatitis or FPD) has been reported in broiler chickens, attributed to caustic faeces, high humidity, and poor environmental conditions during indoor rearing, preventable by adequate ventilation and husbandry. This is consistent with puffinosis being observed in Shearwater nesting burrows situated in tall, dense, vegetation (e.g., bracken Pteridium aquilinum) but rarely reported in burrows situated in well-ventilated, short coastal grasslands. This proposed environmental aetiology accounts for the disease’s non-epizootic prevalence, spatial variation within colonies, and higher frequency in chicks that are restricted to nesting burrows.